Penerapan Komunikasi Persuasif Pimpinan untuk Meningkatkan Kedisiplinan dan Motivasi Mahasiswa di STAI-YDI Lubuk Sikaping - Dafrizal Dafrizal; Sarmiati Sarmiati (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This research discusses the case of lack of discipline among students at STAI-YDI Lubuk Sikaping, particularly in terms of attendance and payment of tuition fees, which have negative impacts on students' motivation and achievement. This lack of discipline is also caused by disrupted operational activities on the campus. The purpose of this research is to analyze the persuasive communication process of the leaders in motivating students to achieve and discipline them at STAI-YDI Lubuk Sikaping. This research uses a case study approach, which is an approach in qualitative research. This research uses observation and in-depth interviews with leaders and students as informants to collect data. The primary data obtained will be analyzed to find effective solutions in improving discipline and motivation among students on the campus. The persuasive processes carried out by the leaders must be done regularly and periodically to achieve effectiveness and maximum results. In this case, improving students' discipline and motivation is crucial to maintain the expected academic quality and achievement